Controlling Terahertz Surface Plasmon Properties on a Periodically Structured Silicon Surface - Gagan Kumar (Journal of Spectroscopy)
The paper presents experimental and numerical investigations on the terahertz (THz) surface plasmon propagation in a periodically patterned doped silicon substrate. Silicon substrates are periodically patterned with 2D array of vertical structures forming a plasmonic waveguide. The waveguide configurations are found to support resonant surface modes at certain frequencies which can occur anywhere depending on the structural parameters. The 2D pattern of vertical structures is observed to affect the THz surface plasmon propagation along the waveguide configuration. The periodicities are changed in both directions to examine the change in amplitude and cut-off frequencies of the resonant surface modes. The results are confirmed independently through finite element method based numerical simulations and compared with theory. The present study should find applications in facilitating the development of futuristic ultrahigh speed networks and devices operating at the terahertz frequencies.